2021
DOI: 10.3390/antibiotics10070772
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Profiles and Genes of Staphylococci Isolated from Mastitic Cow’s Milk in Kenya

Abstract: Increasing numbers of potentially zoonotic multidrug-resistant (MDR) staphylococci strains, associated with mastitis in dairy cows, are being reported globally and threaten disease management in both animal and human health. However, the prevalence and antimicrobial resistance profiles of these strains, including methicillin-resistant staphylococci (MRS), in Kenya is not well known. This study investigated the drug resistance profiles and genes carried by 183 staphylococci isolates from 142 dairy cows represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
(118 reference statements)
1
10
1
1
Order By: Relevance
“…This study did not report the presence of the ermB gene from the animal samples (raw milk) or the qnrS gene from human samples (skin swab of the farmer). Contrastingly, previous studies reported the presence of the antibiotic resistance genes ermB and qnrS from animal and human samples, respectively (Abdu and Mirabeau 2019;Mbindyo et al 2021). There is a discrepancy between ARGs and phenotypic confirmation.…”
Section: Antibiotic Resistance Marker Genecontrasting
confidence: 62%
See 1 more Smart Citation
“…This study did not report the presence of the ermB gene from the animal samples (raw milk) or the qnrS gene from human samples (skin swab of the farmer). Contrastingly, previous studies reported the presence of the antibiotic resistance genes ermB and qnrS from animal and human samples, respectively (Abdu and Mirabeau 2019;Mbindyo et al 2021). There is a discrepancy between ARGs and phenotypic confirmation.…”
Section: Antibiotic Resistance Marker Genecontrasting
confidence: 62%
“…This finding is in line with the results of previous research in Surabaya, Indonesia (Tyasningsih et al 2019). A study by Mbindyo et al (2021) reported the frequency of resistance to antibiotics ampicillin (71.4%), tetracycline (21%), erythromycin (25.2%) in Kenya. Meanwhile, a previous study by Liu et al 2017 reported the incidence of resistance to antibiotics penicillin G (85.2%), ampicillin (79.6%), tetracycline (13%), and erythromycin (46.3%) in China.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…This alarming rate of resistance to beta-lactam antibiotics is corroborated by some recent findings [ 54 , 55 ] and can be explained by the common use of β -lactams in the treatment of bovine mastitis [ 56 ]. A study carried out in Kenya by Mbindyo et al found that 71.4% of S. aureus strains exhibited resistance to ampicillin [ 57 ]. Another study reported that the frequency of resistance to penicillin G was 85.2% [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a Brazilian study found a lower prevalence of S. aureus isolates (29%) (Kayili and Sanlibaba 2020;Pereira et al 2018). Several efflux pump genes are identified as responsible for MDR mechanisms (Mahmood et al 2016;Mbindyo et al 2021). The presence of a non-native gene involved in the peptidoglycan biosynthesis pathway and producing penicillin-binding proteins (PBPs), a meshlike polymer surrounding the bacterial cell, has also been suggested as a possible explanation for the high prevalence of S. aureus resistance occurrences (Peacock and Paterson 2015;Stapleton and Taylor 2002).…”
Section: Discussionmentioning
confidence: 99%